Cadre Participation in Posyandu Activities - Miguel, Fernando (International Journal of Health Sciences, 2023)
Integrated Healthcare Center is a community-based health vehicle that provides services for 5 main activities, namely Maternal and Child Health, Family Planning, Nutrition, Immunization and P2 Deare which are carried out from, by, for and with the community. The role of cadres is very important because cadres are responsible for implementing the Integrated Healthcare Center program. (Ministry of Health, RI 2018). This research method is a descriptive analytic with a cross-sectional study design, namely a research design designed to perform data analysis that frequently occurs or is ongoing in the study population, with a causal relationship model. The results of this study based on the level of knowledge of the respondents showed that out of 20 respondents, 15 people (75%) had good knowledge and 5 people (25%) had less knowledge. The discussion shows that based on the analysis it shows that the respondents who have good knowledge and good Integrated Healthcare Center cadres are active as many as 7 people (35%). While respondents who had good knowledge and less incidence of dermatitis were 4 people (20%). And the respondents who had less knowledge and active Integrated Healthcare Center cadres were as many as 4 people (20%). The results of statistical tests using the chi-Square test were p = 0.004 with a significance level of α = 0.05 which means p <0.05 then ha is accepted and ho is rejected, thus there is a relationship between knowledge and the activity of Integrated Healthcare Center cadres.